دراسة عددية ثلاثية الأبعاد للسلوك الزلزالي وللتأثير المتبادل “ تربة – أوتاد – منشأ ” بطريقة العناصر المنتهية - اسطة, رامي; حسن, مالك (Latakia University Journal -Engineering Sciences Series, 2014)
يتناول هذا البحث دراسة سلوك الأوتاد تحت تأثير الحمولات الزلزالية من خلال نمذجة فراغية (3D) باستخدام طريقة العناصر المنتهية (FEM) – برنامج (ABAQUS) مع إجراء دراسة متغيرات لأهم المعاملات المؤثرة على الانتقالات والقوى الداخلية المتولدة في الأوتاد. لقد تم إنجاز البحث على مرحلتين: في المرحلة الأولى تم دراسة حالة وتد منفرد (حالة مرجعية)، حيث تم دراسة سلوك وتد منفرد يسند منشأ تم نمذجته بجملة ذات درجة حرية واحدة. أظهرت نتائج الدراسة البارامترية أن وجود المنشأ يسبب تطبيق حمولة كبيرة في الجزء العلوي من الوتد ناتجة عن أثر العطالة ويكون طاغياً على الأثر الحركي، وأن قوى العطالة تزداد بزيادة كتلة المنشأ, وعندما يكون التردد الأساس للمنشأ قريب من تردد الحمولة الزلزالية. أما المرحلة الثانية فتناولت دراسة حالة مجموعة أوتاد، حيث تم دراسة تأثير عدد الأوتاد وتباعداتها ومواقعها على القوى الداخلية والانتقالات المتولدة في الأوتاد، وقد أظهرت نتائج الدراسة البارامترية لهذه المرحلة من البحث أن زيادة عدد الأوتاد في المجموعة تسبب زيادة كبيرة للقوى الداخلية المتولدة في رأس الوتد وتناقصاً طفيفاً لهذه القوى في الجزء الوسطي من الوتد، كما لوحظ عدم توزع الحمولات الزلزالية بشكل متساوٍ على جميع الأوتاد فالأوتاد الركنية تخضع لأكبر قوى بينما الأوتاد الوسطية تخضع لأقل قوى. This research deals with the study of the behavior of piles under the influence of seismic loads through (3D) modeling using FE-Method-program (ABAQUS), with special reference to the most important parameters affecting the displacements and internal forces generated in piles. This study has been completed in two phases: the first phase is a case study of the single Pile (reference case), where a study of the behavior of a single pile assigning structure is modeled with a degree of freedom. The parametric study results show that the presence of structure causes the application of a large load in the upper part of the pile resulting from the impact of inertia dominating the kinetic effect. The forces of inertia increases with the increasing mass of structure, and when the frequency of structure nears the frequency of seismic load. The second phase deals with the study of the situation of the group of piles, where the study handles the effect of a number of piles, piles spacing, and locations on the internal force and displacements generated in the piles. The parametric study results have shown for this phase of this research that an increase the number of piles in the group causes a significant increase of internal forces generated at the top of the pile and a slight decrease for those forces in the central part of the pile, that seismic loads are not distributed equally for all piles, and that corner piles are subject to greater loads while mid. Piles are subject to less load.